Graphene-Based Materials for Photoanodes in Dye-Sensitized Solar Cells - Guo, Xiaoru; Lu, Ganhua; Chen, Junhong (Frontiers in Energy Research, 2015)
This article reviews the research on the use of graphene and related materials in the photoanode of dye-sensitized solar cells (DSSCs). Graphene-based materials, such as pristine graphene, graphene oxide, and reduced graphene oxide, have properties attractive for various components of the DSSC photoanode. We first provide a brief introduction to graphene properties and analyze requirements for making a high-performance photoanode. Then, we introduce applications of graphene-based materials in each part of the DSSC photoanode, i.e., the transparent conducting electrode, the sensitizing material, and the semiconducting layer. Particularly, we discuss how the incorporation of graphene-based materials in those components can enhance the photoanode performance. It is clear that the outstanding properties of graphene, such as the fast electron transfer ability, high Young’s modulus, and good transparency, benefit DSSC photoanode research, and doping or surface modifications of graphene nanosheets with other materials can also improve the photoanode and, thus, the resulting cell performance. Finally, we present an outlook for current issues and further trends for using graphene materials in DSSC photoanodes.